RESOURCES FOR PREVENTING PRESSURE INJURIES: METHODOLOGICAL STUDY TO DEVELOP AND VALIDATE A SCALE - Tonole, Renato; Brandão, Euzeli da Silva; Lanzillotti, Regina Serrão; Cavalcanti, Ana Carla Dantas (Cogitare Enfermagem, 2023)
Objective: To develop and validate a scale for evaluating human and material resources from the perspective of preventing pressure injuries in medical and surgical wards. Method: Methodological study was conducted in three stages: integrative review, elaboration, and validation using the Delphi technique, with eight nurses specializing in dermatology from different states in Brazil from November 2018 to January 2019. They assessed 32 items relating to human and material resources in intermediate care and high-dependency patients. A minimum content validity index of 0.80 was used for validation. Results: In the intermediate care scenario, all items reached 0.77 in the first phase and 0.93 in the second phase. In high dependency, they reached 0.74 in the first phase and 0.84 in the second phase. Conclusion: The scale will allow the assessment of the situational diagnosis of the wards from the perspective of pressure injury prevention.